Local Government Policy in BPHTB Tax Picking Up On the Transaction Sale and Purchase of Land And / Or Building - Catur Agung Bintoro; Amin Purnawan (Jurnal Akta, 2019)
The purpose of this study were 1) For the Local Government Policy in BPHTB Tax Picking Up On the Transaction Sale and Purchase of Land and / or Building 2) To know Constraints faced by the Notary and PPAT in Tax levy BPHTB Purchase Transactions Over Land And / Or Building method used is empirical juridical approach in order to obtain adequate results. Specifications research used in this study is a descriptive analysis, from this study is expected to obtain a detailed and systematic description of the problem to be studied. Based on data analysis concluded that: 1) The policy conducted by the Central Government is to give broad authority to manage their own household, including the authority to explore potential financial income areas one of which is the local tax. BPHTB tax requires that the buying and selling prices reported are approaching the fair market value of that property. It is sometimes difficult to implement given the magnitude of the price of the transaction will affect the costs associated with the transaction. 2) Some of the obstacles faced by the Notary and PPAT The BPHTB levying taxes as dishonest taxpayers to include the value of the transaction, the clerk is still difficult and takes a long time in the field verification process, lack of transparency in the market price of land, lack of good ithikad the seller, as well as the lack of public knowledge about this BPHTB tax.Keywords: Policies; Local Government; Tax; BPHTB; Transactions.